Incidence and predictors of tuberculosis among HIV-positive adults on antiretroviral therapy at Debre Markos referral hospital, Northwest Ethiopia: a retrospective record review - Belisty Temesgen; Getiye Dejenu Kibret; Nakachew Mekonnen Alamirew; Mamaru Wubale Melkamu; Yitbarek Tenaw Hibstie; Pammla Petrucka; Animut Alebel (BMC, 2019)
Abstract Background Tuberculosis is the leading cause of morbidity and mortality among people living with human immunodeficiency virus. Almost one-third of deaths among people living with human immunodeficiency virus are attributed to tuberculosis. Despite this evidence, in Ethiopia, there is a scarcity of information regarding the incidence and predictors of tuberculosis among people living with HIV. Thus, this study assessed the incidence and predictors of tuberculosis among HIV-positive adults on antiretroviral therapy. Methods This study was a retrospective record review including 544 HIV-positive adults on antiretroviral therapy at Debre Markos Referral Hospital between January 1, 2012 and December 31, 2017. The study participants were selected using a simple random sampling technique. The data extraction format was adapted from antiretroviral intake and follow-up forms. Cox-proportional hazards regression model was fitted and Cox-Snell residual test was used to assess the goodness of fit. Tuberculosis free survival time was estimated using the Kaplan-Meier survival curve. Both the bi-variable and multivariable Cox-proportional hazard regression models were used to identify predictors of tuberculosis. Results In the final analysis, a total of 492 HIV-positive adults were included, of whom, 83 (16.9%) developed tuberculosis at the time of follow-up. This study found that the incidence of tuberculosis was 6.5 (95% CI: 5.2, 8.0) per 100-person-years (PY) of observation. Advanced World Health Organization clinical disease stage (III and IV) (AHR: 2.1, 95% CI: 1.2, 3.2), being ambulatory and bedridden (AHR: 1.8, 95% CI: 1.1, 3.1), baseline opportunistic infections (AHR: 2.8, 95% CI: 1.7, 4.4), low hemoglobin level (AHR: 3.5, 95% CI: 2.1, 5.8), and not taking Isonized Preventive Therapy (AHR: 3.9, 95% CI: 1.9, 7.6) were found to be the predictors of tuberculosis. Conclusion The study found that there was a high rate of tuberculosis occurrence as compared to previous studies. Baseline opportunistic infections, being ambulatory and bedridden, advanced disease stage, low hemoglobin level, and not taking Isonized Preventive Therapy were found to be the predictors of tuberculosis. Therefore, early detection and treatment of opportunistic infections like tuberculosis should get a special attention.